Nuprl Lemma : hdf-bind-gen-ap-eq
∀[A,B,C:Type]. ∀[X:hdataflow(A;B)]. ∀[Y:B ⟶ hdataflow(A;C)]. ∀[hdfs:bag(hdataflow(A;C))]. ∀[a:A].
  X (hdfs) >>= Y(a)
  = <fst(X(a)) ([y∈bag-map(λP.(fst(P(a)));hdfs + bag-map(Y;snd(X(a))))|¬bhdf-halted(y)]) >>= Y
    , ⋃p∈bag-map(λP.P(a);hdfs + bag-map(Y;snd(X(a)))).snd(p)
    >
  ∈ (hdataflow(A;C) × bag(C)) 
  supposing valueall-type(C)
Proof
Definitions occuring in Statement : 
hdf-bind-gen: X (hdfs) >>= Y
, 
hdf-halted: hdf-halted(P)
, 
hdf-ap: X(a)
, 
hdataflow: hdataflow(A;B)
, 
valueall-type: valueall-type(T)
, 
bnot: ¬bb
, 
uimplies: b supposing a
, 
uall: ∀[x:A]. B[x]
, 
pi1: fst(t)
, 
pi2: snd(t)
, 
lambda: λx.A[x]
, 
function: x:A ⟶ B[x]
, 
pair: <a, b>
, 
product: x:A × B[x]
, 
universe: Type
, 
equal: s = t ∈ T
, 
bag-combine: ⋃x∈bs.f[x]
, 
bag-filter: [x∈b|p[x]]
, 
bag-append: as + bs
, 
bag-map: bag-map(f;bs)
, 
bag: bag(T)
Definitions unfolded in proof : 
uall: ∀[x:A]. B[x]
, 
member: t ∈ T
, 
uimplies: b supposing a
, 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
subtype_rel: A ⊆r B
, 
so_lambda: λ2x.t[x]
, 
so_apply: x[s]
, 
top: Top
, 
prop: ℙ
, 
pi2: snd(t)
Latex:
\mforall{}[A,B,C:Type].  \mforall{}[X:hdataflow(A;B)].  \mforall{}[Y:B  {}\mrightarrow{}  hdataflow(A;C)].  \mforall{}[hdfs:bag(hdataflow(A;C))].  \mforall{}[a:A].
    X  (hdfs)  >>=  Y(a)
    =  <fst(X(a))  ([y\mmember{}bag-map(\mlambda{}P.(fst(P(a)));hdfs  +  bag-map(Y;snd(X(a))))|\mneg{}\msubb{}hdf-halted(y)])  >>=  Y
        ,  \mcup{}p\mmember{}bag-map(\mlambda{}P.P(a);hdfs  +  bag-map(Y;snd(X(a)))).snd(p)
        > 
    supposing  valueall-type(C)
Date html generated:
2016_05_16-AM-10_43_11
Last ObjectModification:
2015_12_28-PM-07_43_08
Theory : halting!dataflow
Home
Index